Empowerment in the Pandemic Era: The Role of Corporate Social Responsibility (CSR) in Industry Survive in Indonesia - Andina Nur Fathonah (International Journal of Economics (IJEC), 2022)
The Covid-19 pandemic which began at the end of 2019 has not yet passed, several industries are still surviving, namely food, pharmaceuticals and hospitals, technology, financial services and education. This is what encourages companies to carry out Corporate Social Responsibility (CSR) strategies and maybe even change the plans that were planned the previous year. The research method used is qualitative with analytical description. There are 20 companies engaged in the Food and Beverage sector in 2020 which report CSR reports from 26 companies in their Annual Reports. Only 4 companies that do not specialize in CSR for Covid-19, the remaining 16 companies have taken concrete actions for employees and the community.